2020
DOI: 10.1016/j.heliyon.2020.e05331
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal and histopathology effect of endophytic fungal extracts of Aspergillus tamarii against Aedes aegypti and Culex quinquefasciatus

Abstract: Background Mosquitoes biolarvicides remain the most important method for mosquito control. The previous studies have shown Aspergillus sp. -expressed larvicidal properties against mosquito species. The present study evaluated larvicidal and histopathological effect of an endophytic fungus Aspergillus tamarii isolated from theCactus stem ( Opuntia ficus-indica Mill) . Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…The ethyl acetate extract of Fusarium equiseti ef-2, an endophytic fungus, had significant larvicidal activity against Culex mosquito larvae. This complements recent findings that used the same ethyl acetate extract of another endophytic fungus, Aspergillus tamarii, against two mosquito larvae, Aedes aegypti and Culex quinquefasciatus 47 . The ethyl acetate extract of Cochliobolus spicifer, an endophyte from the date palm Phoenix dactylifera, larvicidal activity against Aedes caspius and Culex pipiens 48 .…”
Section: Discussionsupporting
confidence: 86%
“…The ethyl acetate extract of Fusarium equiseti ef-2, an endophytic fungus, had significant larvicidal activity against Culex mosquito larvae. This complements recent findings that used the same ethyl acetate extract of another endophytic fungus, Aspergillus tamarii, against two mosquito larvae, Aedes aegypti and Culex quinquefasciatus 47 . The ethyl acetate extract of Cochliobolus spicifer, an endophyte from the date palm Phoenix dactylifera, larvicidal activity against Aedes caspius and Culex pipiens 48 .…”
Section: Discussionsupporting
confidence: 86%
“…Silosuh et al (Silo-Suh et al, 1994) isolated a strain of Bacillus cereus UW85 that controlled alfalfa damping-off by inhibiting oomycete pathogens and producing two antimicrobial substances, aminopolyols and aminoglycosides. Baskar et al (2020) isolated and identified an endophytic fungus from the cactus Aspergillus tamarii based on the fact that its mycelial metabolite ethyl acetate has a good insecticidal effect. An efficient system for the bioconversion of sucrose to oligofructose (FOS) was obtained using Aspergillus tamarii NKRC 1229 mycelial fructosyltransferase (Choukade and Kango, 2019).…”
Section: Effect Of Inoculation With Growthpromoting Strains On Tobaccomentioning
confidence: 99%
“…Two strains of A. tamari F2 and A. flavus F3 also showed pathogenicity against the bug Elasmolomus pallens with mortality rates of 62% and 90%, respectively after 10 days at a concentration of 1 × 10 8 conidia/mL (Umaru and Simarani 2020). Also, A. flavus, A. fumigutus, and A.niger showed pathogenicity against three grasshoppers O. velox, P. pictus, and H. nigrorepletus, whereas A. tamari showed pathogenicity against mosquitos Aedes aegypti and Culex quinquefasciatus (Baskar et al 2020). This is the first report of pathogenicity of fungi A. tamarii, B. bassiana, and M. anisopliae against the grasshopper O. chinensis.…”
Section: Discussionmentioning
confidence: 95%
“…has been reported as potential entomopathogenic fungi for the control of various grasshoppers and locusts. A. oryzae showed pathogenicity against the locust L. migratoria, whereas A. flavus, A. fumigutus, and A.niger showed pathogenicity against grasshoppers Oxya velox, P. pictus, and Hieroglyphus nigrorepletus (Zhang et al 2015;Baskar et al 2020). However, there has been little research on entomopathogenic fungi against the grasshopper O. chinensis so far.…”
Section: Introductionmentioning
confidence: 99%